2022
DOI: 10.1007/s10457-022-00789-w
|View full text |Cite
|
Sign up to set email alerts
|

Traditional oases in Northern Africa as multifunctional agroforestry systems: a systematic literature review of the provided Ecosystem Services and of the main vulnerabilities

Abstract: Traditional oases represent unique forms of adaptation to extreme environmental conditions, developed through the centuries by local farmers to support their livelihood, combining different crops (date palms, fruit trees, vegetables and fodder) with livestock breeding. Despite their social, economic and cultural importance, these agroforestry systems are currently facing multiple socio-environmental threats. The aim of the paper is to investigate the variety of Ecosystem Services (ES) and the main threats rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 85 publications
0
14
0
2
Order By: Relevance
“…On average, each palm needs approximately 1093 gallons per month. Santoro [47] also found that the main threat to traditional oases in Northern Africa is water with related issues (desertification, drought, salinization, or overexploitation), whereas the most pressing threat to the US and Mexican date industries is the South American Palm Weevil (SPW) [48]. Other threats identified from the survey were urban expansion (human impact) and soil and palm diseases (Red Palm Weevil (RPW)) (Table 4).…”
Section: Survey Analysismentioning
confidence: 93%
“…On average, each palm needs approximately 1093 gallons per month. Santoro [47] also found that the main threat to traditional oases in Northern Africa is water with related issues (desertification, drought, salinization, or overexploitation), whereas the most pressing threat to the US and Mexican date industries is the South American Palm Weevil (SPW) [48]. Other threats identified from the survey were urban expansion (human impact) and soil and palm diseases (Red Palm Weevil (RPW)) (Table 4).…”
Section: Survey Analysismentioning
confidence: 93%
“…The fruit trees like Carica papaya (Caricaceae), bananas, and fodder trees like Dhaincha (Sesbania aculeata) are commonly also grown near the home. The household head in Rwanda who planted and used L. leucocephala and C. calothyrsus for fodder in their home gardens increased their milk production (Santoro, 2023). Moreover it is also dung for manure, which further improved crop production and household income (Wolpert et al, 2022).…”
Section: Sources: Household Survey 2022mentioning
confidence: 99%
“…Promoting climate-resistant foods such as the date palm aligns with the UN’s Zero Hunger goal, as the date palm seems less affected by climate change [ 86 , 91 ]. Palm groves combat desertification, create a microclimate, preserving agrobiodiversity and support various animal species, benefiting local communities [ 92 , 93 , 94 , 95 ]. Intensive date palm cultivation brings environmental challenges, e.g., leading to soil salinization [ 96 , 97 , 98 , 99 , 100 , 101 ] or reduced livestock presence [ 102 ].…”
Section: Sustainability and Valorization Of Date Palmmentioning
confidence: 99%